The Use of Citation Analysis Detecting the Value of the Information Resources and the Library Institution in the Process of Information Production and Methodology Problem - I - Oya Gürdal Tamdoğan (Türk Kütüphaneciliği)
As it is seen in the application examples in the literature, citation analysis and bibliometric studies are significant instruments to consider in the discipline and at the evaluation stage of products of the process of information production in general. In addition, to this in the treatment, in other words in the methodological approaches of citation analysis and researches based on bibliometrics, taking into consideration the deficiencies in addition to qualifications, it is necessary to put forward its powerful aspects in full as much as possible and eliminate its weak sides and this subject is still open to new methodological approaches. Literature as far as it can be traced has some certain gaps regarding the process of information production of library institution in terms of metrical studies which support its contribu- tions with concrete data. The gap should befilledwith new approaches and methodologies by colleagues engaged in research at the application level and academicians working in the field of our discipline.